Assess the Changing Role of Database Technology within Geographic Information System Over the Past 45 Years - Ashna Abdulrahman Kareem Zada (Polytechnic Journal)
Spatial data stored in databases have been become progressively crucial in the geographic information system (GIS) field within recent years. Spatial data are increasingly being noted for its significance in representing for real-life relationships. The value of spatial databases cannot be underestimated since it has been established to be an efficient and flexible means of handling enormous spatial datasets. This paper shows the different methods, in which spatial data are integrated by major database vendors and database within GIS. The current report has also examined the new technologies and advancements by database and GIS vendors in relational database management systems in the past four decades, which have facilitated spatial data to become integrated into databases.